2-Iodoxybenzenesulfonic Acid-Catalysed oxidation of Primary and Secondary Alcohols with Oxone in Cetyl Trimethylammonium Bromide Micelles at Room Temperature. (July 2014) - Liu, Yangyang; Wang, Boliang
A mild and green protocol for alcohol oxidation using 2-iodoxybenzene sulfonic acid/oxone at room temperature in CTAB micelles has been developed. Typically, secondary benzyl alcohols were oxidised to ketones and primary benzyl alcohols to aldehydes in good yields in 2 h. Under harsher conditions (100 °C/24 h), aliphatic alcohols were oxidised to ketones or organic acids in moderate to high yields.